A participatory adoption of improved crop technologies in the savannas of West Africa: empirical study from Borno, Nigeria - Amaza, P.S.; Ellis-Jones, J.; Kamara, A.Y.; Helsen, J.; Gaya, H.I. (African Crop Science Society, 2007)
A Participatory Impact assessment (PASS) was undertaken to evaluate the adoption of improved crop technologies by farmers in the savannas of Borno State, Nigeria. A total of 476 people including 288 men and 188 women participated in PASS. These included representatives of 97 farmer groups/CBOs, out of a total of 287 such groups with which IITA is presently working. PASS measured adoption in three ways, firstly through discussion with participating groups, secondly with a number of key individual farmers and lastly, through transect walks through arable areas. The results revealed that improved maize and soybean varieties had the highest adoption rates, with maize (83%) and soybean (68%). Women farmers had adopted at higher rates than men. Farmers adopting the new technologies indicated they achieved yield increases ranging from 20-100% and benefits included: - improved food security (84%), increased sale of crops (69%), increased livestock sales (18%), increased incomes (62%), improved household nutrition largely from soybeans (71%), improved health (61%), increased expenditure on education (45%) and housing (29%). The policy implication is that government should play a greater role at improving rural infrastructures, reducing the cost of doing business and strengthening regulatory mechanisms.